Myogenic commitment of human stem cells by myoblasts Co-culture: a static vs. a dynamic approach. Issue 1 (31st December 2022) - Scala, Pasqualina; Lovecchio, J.; Lamparelli, E.P; Vitolo, R.; Giudice, V.; Giordano, E.; Selleri, C.; Rehak, L.; Maffulli, N.; Della Porta, G.
Abstract: An in-vitro model of human bone marrow mesenchymal stem cells ( h BM-MSCs) myogenic commitment by synergic effect of a differentiation media coupled with human primary skeletal myoblasts ( h SkMs) co-culture was developed adopting both conventional static co-seeding and perfused culture systems. Static co-seeding provided a notable outcome in terms of gene expression with a significant increase of Desmin (141-fold) and Myosin heavy chain II (MYH2, 32-fold) at day 21, clearly detected also by semi-quantitative immunofluorescence. Under perfusion conditions, myogenic induction ability of h SkMs on h BM-MSCs was exerted by paracrine effect with an excellent gene overexpression and immunofluorescence detection of MYH2 protein; furthermore, due to the dynamic cell culture in separate wells, western blot data were acquired confirming a successful cell commitment at day 14. A significant increase of anti-inflammatory cytokine gene expression, including IL-10 and IL-4 (15-fold and 11-fold, respectively) at day 14, with respect to the pro-inflammatory cytokines IL-12A (7-fold at day 21) and IL-1β (1.4-fold at day 7) was also detected during dynamic culture, confirming the immunomodulatory activity of h BM-MSCs along with commitment events. The present study opens interesting perspectives on the use of dynamic culture based on perfusion as a versatile tool to study myogenic events and paracrine cross-talk compared to the simple co-seeding static culture.